A comprehensive review of bioactive peptides from marine fungi and their biological significance - Youssef, Fadia S.; Ashour, Mohamed L.; Singab, Abdel Nasser B.; Wink, Michael (Marine drugs, 2019)
Fungal marine microorganisms are a valuable source of bioactive natural products. Fungal secondary metabolites mainly comprise alkaloids, terpenoids, peptides, polyketides, steroids, and lactones. Proteins and peptides from marine fungi show minimal human toxicity and less adverse effects comparable to synthetic drugs. This review summarizes the chemistry and the biological activities of peptides that were isolated and structurally elucidated from marine fungi. Relevant fungal genera including Acremonium, Ascotricha, Aspergillus, Asteromyces, Ceratodictyon, Clonostachys, Emericella, Exserohilum, Microsporum, Metarrhizium, Penicillium, Scytalidium, Simplicillium, Stachylidium, Talaromyces, Trichoderma, as well as Zygosporium were extensively reviewed. About 131 peptides were reported from these 17 genera and their structures were unambiguously determined using 1D and 2D NMR (one and two dimensional nuclear magnetic resonance) techniques in addition to HRMS (high resolution mass spectrometry). Marfey and Mosher reactions were used to confirm the identity of these compounds. About 53% of the isolated peptides exhibited cytotoxic, antimicrobial, and antiviral activity, meanwhile, few of them showed antidiabetic, lipid lowering, and anti-inflammatory activity. However 47% of the isolated peptides showed no activity with respect to the examined biological activity and thus required further in depth biological assessment. In conclusion, when searching for bioactive natural products, it is worth exploring more peptides of fungal origin and assessing their biological activities.